Association of resistin level with acanthosis nigricans in obese adolescents - Dini Noviarti; Eka Agustia Rini; Fadil Oenzil (Paediatrica Indonesiana, 2016)
Background Childhood obesity is associated with increased risk of cardiovascular diseases and metabolic syndrome, such as insulin resistance. Clinically, insulin resistance may be manifested as acanthosis nigricans. Resistin has a biological activity that is important in glucose and lipid metabolisms and closely related to the incidence of insulin resistance.Objective To find out the association of resistin level with scale of acanthosis nigricans in adolescents obesity.Methods A cross-sectional study was conducted on 53 obese adolescents with acanthosis nigricans in senior high schools in Padang, West Sumatera. Degree of acanthosis nigricans was assessed using scale of Burke and then plasma resistin level was performed with ELISA. Data were analyzed using ANOVA and post-hoc test.Result The mean of resistin level in obese adolescents was 14.21 (SD 7.43) ng/dL. High resistin level was found in scale of acanthosis nigricans 2,3 and 4 (P=0.0001). Obese adolescents with severe degree of acanthosis nigricans has higher resistin level compared to milder acanthosis nigricans.Conclusion In obese adolescents, the higher degree of acanthosis nigricans, the higher level of plasma resistin.